Level of Service Evaluation of Pedestrian Facility in Tourism Area: Case Study Jalan Braga, Bandung - Christine, Christine; Rifai, Andri Irfan; Handayani, Susanty (DAS Institute, 2022)
Jalan Braga is a modern tourist area located in the center of Bandung City with its strategic location and being in the middle of the city invites many visitors with various modes of transportation to pass through the road. The uniqueness of this street lies in its distinctive pedestrian street with Dutch heritage buildings and paintings made by the Bandung painting artist community, which affect the level of pedestrian service. This study was structured to evaluate the service level of existing Pedestrian Facilities referring to the Technical Planning Guidelines. The analytical method used is Index Performance Analysis by comparing the value of Performance and Interest in Pedestrian Facilities in the City of Bandung. The research results show that the average performance index is 4.40, the average interest index is 3.00, and the average GAP is 1.19. Most suggestions were obtained for increasing the comfort of the pedestrians and the availability of seating facilities.